Left-Wing Xenophobia in Europe - Kopyciok, Svenja; Silver, Hilary (Frontiers in Sociology, 2021)
Given rising populist nationalism and multiplying meanings of “right” and “left,” this paper assesses whether Europeans who identify as extremely left-wing on the political spectrum hold anti-immigrant attitudes. In contrast to right-wing xenophobes, we further examine whether the political left, who conventionally emphasize class conflict, oppose immigrants less for cultural reasons and more for materialist reasons. We also consider whether socioeconomic status and values traditionally associated with the political left – favoring redistributive policies, egalitarianism, or social rights to benefits and services for immigrants – temper left- more than right-wing xenophobia. We find that a surprisingly large share of those who identify as far left do express extremely xenophobic attitudes, and we profile them in contrast to far right xenophobes. With logistic regression analysis of nine waves of the European Social Survey (2002-2018), we find that, all things equal, socioeconomic status influences far left xenophobia more than far right xenophobia, but inegalitarian values, less support for redistributive policies, and welfare chauvinism can only partially account for far left xenophobia and unexpectedly do not distinguish it from far right xenophobia. This implies that far left parties might adopt or anti-immigrant policies to try to retain their loyal voters, even though such policies do not comport with broader left-wing values and may increase racial and ethnic inequality. Controlling for demographic and attitudinal differences reduces the probability of xenophobia among the far left by about sixty percent, but there remains some residual anti-immigrant attitudes among this group still to be explained.